The sesquicentennial of the distribution of the English debt among the member states that were part of Gran Colombia - Villacrés Moscoso, Jorge (Revista Universidad de Guayaquil, 1988)
In the month of April 1838, the Plenipotentiaries of New Granada, Venezuela and Ecuador met in Bogotá for the definitive distribution of what had constituted the English Debt, therefore, it is in this year that the Sesquicentennial is commemorated. The increasing expenses incurred in the fights for freedom led the Colombian Government to manage fabulous loans in England, in order to cover the most urgent needs that the war imposed. The Liberator entrusted the delicate mission of contracting such loans to Francisco Antonio Zea from Antioquia, the same one who went to London in 1820, invested with the rank of Plenipotentiary Minister and Extraordinary Envoy. He was empowered, according to the Agreement, to contract loans, up to one hundred million Pounds Sterling.